2020
DOI: 10.3389/fphy.2020.00311
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Infection Rate and Predictions of Disease Spreading Based on Initial Individuals Infected With COVID-19

Abstract: We consider the pandemic spread of COVID-19 in selected countries after the outbreak of the SARS-CoV-2 coronavirus in Wuhan City, China. We estimated the infection rate and the initial individuals infected with COVID-19 by using officially reported data from the early stages of the epidemic for a model of susceptible (S), infectible (I), quarantined (Q), and officially confirmed recovered (R k) populations (the so-called SIQR k model). In the officially reported data, we know the number of quarantined cases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The incubation period of the coronavirus disease (after which symptoms develop) for infected individuals is found to be in the range of 8.2–15.6 days at the percentile level [30] . Furthermore, recent studies have shown that COVID-19 recovery times have an average value of about 25–28 days [31] , [32] . Given that these recovery times are evaluated after symptoms develop, a total of 35 days after infection is a reasonably accurate estimate.…”
Section: The Random Walk Monte Carlo Methodsmentioning
confidence: 99%
“…The incubation period of the coronavirus disease (after which symptoms develop) for infected individuals is found to be in the range of 8.2–15.6 days at the percentile level [30] . Furthermore, recent studies have shown that COVID-19 recovery times have an average value of about 25–28 days [31] , [32] . Given that these recovery times are evaluated after symptoms develop, a total of 35 days after infection is a reasonably accurate estimate.…”
Section: The Random Walk Monte Carlo Methodsmentioning
confidence: 99%
“…Since the first confirmed case in 2019, the confirmed COVID-19 cases in all world were rapidly increased, which reached 86.7 million cases, including 1.87 million deaths by January 2021. Determining the future severity of the outbreak is considered one of the main keys to plan against this pandemic [ 85 , 86 ]. In this subsection, we survey the studies that are concerned with analyzing the epidemic status, measure the reproduction number and exponential growth using statistical and DL models.…”
Section: The Study Taxonomymentioning
confidence: 99%
“…The recovered rate is based on 14 days recovery with 96% recovered; i.e., 0.96 . Initial/Parameter Case I/Reference Case II/Reference S(0) 0.97286 [12] 0.994 [12] E(0)+I(0) 0.00905 [41] 3.813 × 10 −4 [41] R(0) 0.01809 [41] 5.569 × 10 −3 [41] β 0.462 [42] 0.32 [43] α 1/11.5 per day [22] 1/11.5 per day [22] γ 0.0686 per day [12] 0.0686 per day [12] b 0 3.178 × 10 −5 per day [44] 4.893 × 10 −5 per day [45] d 0 2.377 × 10 −5 per day [46] 1.992 × 10 −5 per day [47] d 1 2.585 × 10 −5 per day [12] 2.021 × 10 −5 per day [41] d 2 2.585 × 10 −5 per day [12] 2.021 × 10 −5 per day [41] …”
Section: Numerical Simulations and Interpretation Of The Modelmentioning
confidence: 99%